Final answer:
To solve the system of equations, we can substitute the expression for x from the first equation into the second equation and solve for y. Then, substitute the value of y into the first equation to solve for x. The solution is (x, y) = (-7, -5).
Step-by-step explanation:
To find the solution (x, y) to the system of equations, we can use the method of substitution or elimination. Let's use the method of substitution.
- From the first equation, we can isolate x by subtracting 2y from both sides: x = -17 - 2y.
- Substitute this expression for x in the second equation: 5(-17 - 2y) - 4y = -15.
- Simplify and solve for y: -85 - 10y - 4y = -15. Combine like terms: -14y = 70. Divide both sides by -14 to solve for y: y = -5.
- Substitute the value of y into the first equation to solve for x: 2(-5) + x = -17. Simplify: -10 + x = -17. Add 10 to both sides: x = -7.
Therefore, the solution to the system of equations is (x, y) = (-7, -5).